PENGELOLAAN KEUANGAN DI YAYASAN DARUL ISLAM AL BANTANI SERANG BANTEN - Yulyanah, Yulyanah; Rahmawati, Titah; Fathimah, Siti Nurul (Jurnal Pajak Populis, 2025)
The community service program conducted at the Darul Islam Al Bantani Serang Foundation aims to improve the understanding of financial preparation and management for the Foundation’s administrators, making them more professional and able to account for donations in accordance with applicable regulations regarding non-profit organizations (ISAK 35). This activity has several stages in its implementation, including introduction to the situation, description/description of the area where the service is held, preparation of activities, implementation and evaluation. The participants were enthusiastic in participating in the activities carried out by lecturers of applied tax accounting undergraduates at Pamulang University. The training was conducted interactively through lectures, discussions, case simulations, and direct practice. It is hoped that through this approach, managers will be able to implement a better financial system that can be accounted for administratively. The results of this service are expected to provide a real contribution to capacity development in foundation financial management and become a model for empowering educational institutions.